2011
DOI: 10.1017/s1368980011001133
|View full text |Cite
|
Sign up to set email alerts
|

Parent calcium-rich-food practices/perceptions are associated with calcium intake among parents and their early adolescent children

Abstract: Objective: The study aimed to (i) segment parents of early adolescents into subgroups according to their Ca-rich-food (CRF) practices and perceptions regarding early adolescent CRF intake and (ii) determine whether Ca intake of parents and early adolescents differed by subgroup. Design: A cross-sectional convenience sample of 509 parents and their early adolescent children completed a questionnaire in 2006-2007 to assess parent CRF practices and perceptions and to estimate parent and child Ca intakes. Setting:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 42 publications
2
13
0
Order By: Relevance
“…Older age had a small but significant association with higher health ratings for unsweetened, minimally processed beverages, in line with our hypotheses and previous research (Pollard et al, 2016;Reicks et al, 2012). The presence of children (aged 0-12 years) had a small but significant positive association with health ratings of sweetened, processed beverages and a negative association with perceptions of unsweetened, minimally processed drinks (aged 0-5 years), both of which were contrary to our expectations.…”
Section: Demographic Associationssupporting
confidence: 64%
See 2 more Smart Citations
“…Older age had a small but significant association with higher health ratings for unsweetened, minimally processed beverages, in line with our hypotheses and previous research (Pollard et al, 2016;Reicks et al, 2012). The presence of children (aged 0-12 years) had a small but significant positive association with health ratings of sweetened, processed beverages and a negative association with perceptions of unsweetened, minimally processed drinks (aged 0-5 years), both of which were contrary to our expectations.…”
Section: Demographic Associationssupporting
confidence: 64%
“…Age and gender may be significant factors in SSB consumption, with younger age groups and men more likely to consume SSBs and be less aware of their negative health impacts (Gravel et al, 2012;Park, Onufrak, Sherry, & Blanck, 2014;Pollard et al, 2016;Rampersaud et al, 2014;Reicks et al, 2012). Co-habitation and presence of children in the household has also been associated with diet healthiness and consumption of EDNP products (Elstgeest, Mishra, & Dobson, 2012;Farragher, Wang, & Worsley, 2016).…”
Section: Demographic Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…This outcome contradicted the conclusions of Tornaritis et al [68], who pointed out that the mother’s level of education had greater influence than that of the father’s on the child’s food consumption patterns. Along with the results of this study, Reicks et al [69] indicated that parents play a key role in schoolchildren’s dietary patterns, as parental habits affect children’s eating behavior.…”
Section: Discussionsupporting
confidence: 76%
“…Different factors can affect the consumption of dairy products of a child. Parents influence children's consumption of milk and dairy products, and if they consume more milk, it is very likely that their children will also consume more milk and dairy products (Reicks et al, 2011). Although milk and dairy products are considered to be very important in the diet of children, their consumption is declining, and one of the main reasons is the increased consumption of sweetened soft drinks.…”
Section: Introductionmentioning
confidence: 99%